A new deep-water species of snake eel, Xyrias anjaalai sp. nov. (Anguilliformes: Ophichthidae), from the Western Indian Ocean - Augustina, Treasa A.x; Sreeram, Miriam Paul; Sukumaran, Sandhya; Jose, Anjaly; Sreekumar, K.m. (Zootaxa, 2020)
A new species of snake eel Xyrias anjaalai sp. nov. (Anguilliformes: Ophichthidae) is described from morphological analysis of 12 specimens and molecular analysis of four specimens, caught off Kollam, Kerala, southwestern India, by deep-sea trawling. X. anjaalai is distinguished from its congeners by having a large eye diameter, a short snout, a different dentition pattern as in the 3rd row of maxillary teeth beginning at the level of the 4th vomerine tooth between the two existing rows in the inner series of maxillary teeth, an irregular tooth patch for approximately 1/10th of the lateral side of the dental arch in the distal portion and a vertebral count of predorsal vertebrae 18–21, preanal vertebrae 73–76 and total vertebrae 147–149. Phylogenetic relationships of X. anjaalai with other species in Ophichthidae were examined using partial nucleotide sequences of the COI gene (617 bp). The genetic analyses suggest that the new species is closest to X. revulsus followed by Apterichtus klazingai with Kimura 2 parameter (K2P) values of 0.6 and 2.8% respectively. In the phylogenetic reconstruction, sequences of X. anjaalai formed a distinct clade demonstrating their uniqueness as a separate species.